2010
DOI: 10.1017/s0022112010003095
|View full text |Cite
|
Sign up to set email alerts
|

On the wake-induced vibration of tandem circular cylinders: the vortex interaction excitation mechanism

Abstract: The mechanism of wake-induced vibrations (WIV) of a pair of cylinders in a tandem arrangement is investigated by experiments. A typical WIV response is characterized by a build-up of amplitude persisting to high reduced velocities; this is different from a typical vortex-induced vibration (VIV) response, which occurs in a limited resonance range. We suggest that WIV of the downstream cylinder is excited by the unsteady vortex-structure interactions between the body and the upstream wake. Coherent vortices inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(143 citation statements)
references
References 44 publications
9
127
1
2
Order By: Relevance
“…At the two closest distances, all three shapes the cylinder, the elliptical cylinder, and the whisker show signs of wake induced response, which is similar to trends reported in the literature for cylinders in tandem at similar distances d x /d = 2 to 5.6 [65,5,4,3].…”
Section: Comparison Between the Whisker And The Cylinder And Ellipticsupporting
confidence: 86%
See 1 more Smart Citation
“…At the two closest distances, all three shapes the cylinder, the elliptical cylinder, and the whisker show signs of wake induced response, which is similar to trends reported in the literature for cylinders in tandem at similar distances d x /d = 2 to 5.6 [65,5,4,3].…”
Section: Comparison Between the Whisker And The Cylinder And Ellipticsupporting
confidence: 86%
“…Most research has been conducted in studying two interacting circular cylinders of equal or comparable diameter [65,102,5,4] and it is shown that the upstream cylinder has significant effect on the amplitude and frequency of motion of the downstream cylinder even when it is placed at 25 diameters apart. It was also found that the vortical wake of the upstream cylinder causes a restoring force on the downstream cylinder, which is equivalent to a linear spring, hence affecting its natural frequency [3].…”
Section: Motivationmentioning
confidence: 99%
“…Most research has addressed the problem of two interacting circular cylinders of equal or comparable diameter (Hover & Triantafyllou 2001;Papaioannou et al 2006;Assi et al 2006Assi et al , 2010, in which it was shown that the upstream cylinder has significant effect on the amplitude and frequency of motion of the downstream cylinder even when placed 25 diameters apart. The upstream cylinder continues to have significant effect on the downstream cylinder's response when the two are of unequal diameter and at relatively small distances apart (Sayers & Saban 1994;Lam & To 2003;Assi 2014b;Gao et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies focused on the classical case of flow past two stationary circular cylinders with various arrangements (Meneghini et al 2001;Kang 2003;Sharman et al 2005;Carmo et al 2008;Mussa et al 2009;Sumner 2010). Additionally, the free vibrations (Prasanth and Mittal 2009;Assi et al 2010;Huera-Huarte and Gharib 2011;Carmo et al 2013;Cui et al 2014) and forced vibrations Yang and Zheng 2010;Bao et al 2012;Bao et al 2013;Yang et al 2014) involving two circular cylinders have also been investigated extensively. It was found that the arrangement type and gap spacing have great influences upon the flow dynamics of two-cylinder system.…”
Section: Introductionmentioning
confidence: 99%